Asteroid belt multiple flyby options for M-Class Missions - Sánchez Cuartielles, Joan Pau; Gibbings, Alison; Snodgrass, Colin; Green, Simon F.; Bowles, Neil E. (International Astronautical Federation (IAF), 2016)
Addressing many of the fundamental questions in modern planetary science, as well as in ESA’s cosmic vision, requires a comprehensive knowledge of our Solar System’s asteroid belt. This paper investigates potential opportunities for medium-class asteroid belt survey missions in the timeframe of 2029-2030. The study has been developed in support to CASTAway Asteroid Spectroscopic Survey mission proposal, which is to be submitted to the latest ESA’s medium size mission call. CASTAway envisages the launch of a small telescope with relatively straightforward (i.e. high TRL) remote sensing instrumentation to observe asteroids at a long-range (i.e. point source), but also at a short-range, resolving them at ~10 m resolution. This paper presents a challenging multi-objective optimization problem and discusses the feasibility of such a mission concept. A baseline trajectory is presented that meets both ESA’s medium size mission constraints and the science requirements. The trajectory loops through the asteroid belt during 7 years, visiting 10 objects of a wide range of characteristics, providing sufficient survey time to obtain compositional information for 10,000s of objects and the serendipitous discovery of also 10,000s of 10-m class asteroids. The methodology developed has enabled the exploration of the entire design space for a conservative Soyuz-launch performance, and has found a total of 200 different tour opportunities of the asteroid belt; all compliant with ESA’s 5th call for medium size missions.